A QUALITATIVE STUDY ON MACHINE–HUMAN CO-CREATION: A SECONDARY DATA ANALYSIS OF RESEARCH TRENDS - Mohamed, Sheik; Nirmala, Dr.; Hermansyah, Sam; Wahyuddin, Nur Rahmah (La Ogi : English Language Journal, 2025)
The intersection of artificial intelligence (AI) and human creativity has emerged as a dynamic area of exploration, particularly with the development of generative AI models like GPT-4, DALL·E, and MidJourney. These tools not only automate tasks but also actively contribute to creative processes, resulting in collaborative co-creation between humans and machines. This study investigates the evolving role of AI in creative industries, analyzing secondary data from literature published between 2022 and 2025. By examining key theoretical frameworks, methodologies, and trends, the study identifies the methodological shift from experimental design to reflective frameworks, highlights a lack of unified definitions for co-creation, and emphasizes the growing need to engage with the cultural and ethical implications of AI in creativity. The research contributes to a deeper understanding of machine–human co-creation, its implications for authorship, and the future trajectory of creative partnerships between humans and AI.